Kualitas Pelaksanaan Inisiasi Menyusu Dini Dengan Kecepatan Involusi Uterus Pada Ibu Post Partum - Diah Hapsari Putri; Nunik Hardiwati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2014)
Background: Maternal mortality in Indonesia in 2007 as many as 228 per 100,000 live births, death is common in post-partum period, 50% of the causes of death during childbirth occurred within the first 24 hours. Early Initiation of Breastfeeding is one of the factors that accelerate uterine involution because it stimulates oxytocin which causes the uterus to contract. The aim of research to determine the relationship of the quality of the implementation of Early Initiation of Breastfeeding (IMD) with a speed of maternal uterine involution post partum.Methods: The study design using observational analytic correlational study sites RB Amanda Gamping Sleman, sampling was purposive sampling. Total population data summary maternal outcomes in RB Amanda is 36 people. The instruments used in the form of blank observations. Hypothesis test using product moment correlation test.Results: From the statistical results of product moment correlation test with significance level of 0.05, obtained count r = - 0.023 where there is a very weak negative correlation between the quality of clinical IMD with speed uterine involution post partum mothers in RB Amanda Gamping Sleman.Conclusion: It is suggested to keep health workers in implementing quality IMD.Keywords: Implementation of the IMD, Uterine Involution Speed